ANALISIS PENDAPATAN USAHA PENGGEMUKAN SAPI POTONG YANG MENDAPAT DUKUNGAN KREDIT TUNDA TEBANG (KTT) DI KABUPATEN SEMARANG - Ika Diah Ayu Safitri; Wiludjeng Roessali; Titik Ekowati (University of Jember, 2019)
This study aims to analyze the utilization of delayed logging credit, analyze the R/C ratio, farmer income and net income for farmers who receive and do not receive credit support for fattening beef cattle. The study was conducted in December 2018 - January 2019 in Polosiri Village, Bawen District and Kawengen Village, East Ungaran District, Semarang Regency. Research method is sencus with 31 respondents who received credit support and 37 respondents did not receive credit support. Data were analysed by credit utilization analyze for liverstock and non livestock businesses, R/C ratio, farmer income and net income. Test of different uses of credit received by farmers for liverstock and non for liverstock was carried out using a Paired Sample t-Test and different test R/C ratio, net income and farmers income are carried out using the Independent Sample t-Test. The results showed that the utilization of credit for livestock businesses (52.52%) and non livestock (47.48%), R/C ratio of farmer credit support (1.16) and not credit support (1.13), farmers income of credit support (IDR 585,698/tail of cattle/month) and not credit support (IDR 460,898/tail of cattle/month) there was no significant difference. Net income of farmer credit support (IDR 544,798/tail of cattle/month) and not credit support (IDR 341,727/tail of cattle/month) there are significant differences.